Effect of Metformin on Survival Outcomes in Diabetic Patients with Triple Receptor–Negative Breast Cancer - Bayraktar, Soley (2011)
BACKGROUND: Recent observational studies have shown that metformin use in diabetics decreases both cancer incidence and mortality. Metformin use is also independently predictive of pathologic complete response. We explored the association between metformin use and survival outcomes in patients with triple receptor-negative breast cancer (TNBC) receiving adjuvant chemotherapy. METHODS: The Breast Cancer Management System database of The University of Texas M.D. Anderson Cancer Center identified 1448 women who received adjuvant chemotherapy for TNBC between 1995 and 2007. Patients were categorized by diabetes status and metformin use. Kaplan-Meier product limit method was used to calculate distant metastasis-free survival (DMFS), recurrence-free survival (RFS), and overall survival (OS). Cox proportional hazards models were fit to determine the association between metformin use and survival outcomes. RESULTS: Our study cohort consisted of 63 diabetic patients taking metformin, 67 diabetic patients not taking metformin, and 1318 non-diabetic patients. Patients in the diabetic groups tended to be older (P=0.005); more diabetic patients were postmenopausal (P=0.0007), black (P=0.0001), and obese (P < 0.0001). At a median follow-up of 62 months, there were no significant differences in 5-year DMFS (P=0.23), RFS (P=0.38), and OS (P=0.58) between the three groups. Compared to the metformin group, patients who did not take metformin (Hazard ratio [HR]=1.63; 95% CI:0.87 to 3.06; P=0.13) and nondiabetics (HR=1.62; 95% CI:0.97 to 2.71; P=0.06) tended to have a higher risk of distant metastases. CONCLUSION: Our findings suggest that metformin use during adjuvant chemotherapy does not significantly impact survival outcomes in diabetic patients with TNBC.